Convergence of Regional Human Development Indexes in Poland - Kusideł, Ewa (Comparative Economic Research. Central and Eastern Europe, 2013)
The subject of convergence became popular in Poland upon its accession to the EU in 2004. Since then Poland has been a beneficiary of the cohesion policy – a regional policy of the European Union aimed at increasing the level of economic, social, and territorial (spatial) cohesion. While the economic aspect is a very thoroughly researched area of convergence studies, the social aspects are less often covered by specialist literature. This is the issue raised in this paper which, along with separate measures of social convergence, constructs a region HDI measure to evaluate the social cohesion of Poland’s regions1. Values of regional HDIs in Poland were not known and required calculation, which allowed for drawing conclusions about the standards of living of inhabitants in specific provinces. In general, it was possible to determine that HDIs are rising in all regions, which means, simultaneously, an increase in the standards of living of the provinces’ populations. At the same time, however, that growth was accompanied by increasing divergences in the HDI distribution among regions (sigma-divergence). The study of convergence of specific HDI components also allowed to note that HDI divergences are mainly caused by increasing economic inequalities between regions in Poland (measured by the Gross Domestic Product Index), and inequalities in education (measured by the Education Index).